Dominant Carbapenemase-Encoding Plasmids in Clinical Enterobacterales Isolates and Hypervirulent Klebsiella pneumoniae, Singapore - Melvin Yong; Yahua Chen; Guodong Oo; Kai Chirng Chang; Wilson H.W. Chu; Jeanette Teo; Indumathi Venkatachalam; Natascha May Thevasagayam; Prakki S. Rama Sridatta; Vanessa Koh; Andrés E. Marcoleta; Hanrong Chen; et al. (Emerging Infectious Diseases, 2022)
Dissemination of carbapenemase-encoding plasmids by horizontal gene transfer in multidrug-resistant bacteria is the major driver of rising carbapenem-resistance, but the conjugative mechanics and evolution of clinically relevant plasmids are not yet clear. We performed whole-genome sequencing on 1,215 clinical Enterobacterales isolates collected in Singapore during 2010–2015. We identified 1,126 carbapenemase-encoding plasmids and discovered pKPC2 is becoming the dominant plasmid in Singapore, overtaking an earlier dominant plasmid, pNDM1. pKPC2 frequently conjugates with many Enterobacterales species, including hypervirulent Klebsiella pneumoniae, and maintains stability in vitro without selection pressure and minimal adaptive sequence changes. Furthermore, capsule and decreasing taxonomic relatedness between donor and recipient pairs are greater conjugation barriers for pNDM1 than pKPC2. The low fitness costs pKPC2 exerts in Enterobacterales species indicate previously undetected carriage selection in other ecological settings. The ease of conjugation and stability of pKPC2 in hypervirulent K. pneumoniae could fuel spread into the community.